A Reply to: “Comment on the Fractile Approach to Linear Programming under risk” - Sengupta, J. S. (Management Science, 1970)
A reply to Hazell, P. B. R. 1970. Communications to the editor—Comment on the fractile approach to linear programming under risk. Management Sci. 17(3, November) 236–237.